Color study of the building of the Faculty of Architecture, Urbanism and Arts of the National University of Engineering - Olazábal Furuya, Lorena (2020)
In 2017, the color study of the building of Faculty of Architecture, Urbanism and Arts (FAUA) was carried out in order to recognize the different underlying pictorial strata to know the color palette used in the painting that correspond to the FAUA at the long of the time. This has allowed us to know the different uses and styles used, as well as used techniques and materials used. On the other hand, this type of prospecting has allowed defining the conservation status of certain strata.The use of prospecting techniques, such as the elaboration of stratigraphic samples allow to investigate and study the real estate as a historical document and in turn leave a vestige on the changes that have occurred at the aesthetic and stylistic level.